THE EFFECTIVENESS OF SMALL GROUP DISCUSSION TECHNIQUE TO IMPROVE STUDENTS’ ENGLISH READING COMPREHENSION OF NARRATIVE TEXT - Maulinda Mukhofifah; Nur Ekaningsih (Prominent, 2023)
The purpose of the research was known no matter if use of discussion small group technique was successful in enhancing students reading comprehension of text narrative of tenth graders Sultan Agung 1 Islamic High School Semarang in the academic year 2021/2022. This study was conducted at Sultan Agung 1 Islamic High School Semarang. Located at Jalan Mataram No. 657, Wonodri, Central Java, Indonesia. This kind of the research was experimental quasi. Population in this research was tenth graders of SMA Islam Sultan Agung 1 Semarang. Sample were X MIPA 4 was control class while X MIPA 2 as the experimental class. When gathering data, researcher applied a pre-test and post-test were two tests. The outcome of this research indicated pre-test score means control group 56.42 and experimental group 59.46. Treatment completed, post-test score means control group 69.00 while the means score experimental group 78.58. The outcome indicated a significant dissimilarity both classes in post-test. The outcome analysis t-test was sig (2-tailed) .000 0.05. Thus, it may be said technique small group discussion was efficient was effective to increase readers’ comprehension in students of narrative text.